Assessing tax evasion within an endogenous growth model with productive public expenditure - Tokgöz, Mehmet Emre. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
By setting up an endogenous growth model with productive government expenditures, this thesis analyzes effects of tax rate, deterrence policies, corruption and government externality level on tax evasion decision of economic agents. Moreover, within a Ramsey-type problem, I investigate optimal tax policy, audit rate, and level of public expenditures within an economy that is characterized by tax evasion. The thesis incorporates analytical solutions and supplements them by quantitative analysis by calibration of the model for Turkey. The results show that under the existence of tax evasion, optimal leveI of productive public expenditure would be less than the efficiency level stated in Barro (1990). In addition, existence of tax evasion would not necessarily require higher optima1 tax rates compared to the case of no evasion. In fact, quantitative analysis suggests a lower tax rate. Moreover, optimal conditions do not necessitate complete elimination of tax evasion. The results also show that optimal policies have potential to bring about significant gains on growth rate depending on the positive externality level of public expenditures and the level of corruption in the economy.
Keywords: Tax evasion -- Turkey.